EXERCISE IN FORWARD HEAD POSTURE AND ROUNDED SHOULDER: STRETCHING OR STRENGTHENING? - Hassan, Danish; Irfan, Tehmina; Butt, Salman; Hashim, Muhammad; Waseem, Asna (Annals of Allied Health Sciences, 2022)
Objective: To determine the effects of stretching and strengthening exercises on asymptomatic adults diagnosed with forwarding head posture and rounded shoulders. Material & Methods: A randomized controlled trial was conducted after the screening and confirmation of FHP and RS by measuring craniovetrebreal angle (CVA) and shoulder angle (SA) using Kinovea Software, 34 Patients were inducted into trial through consecutive sampling, with 17 patients in each of 2 groups i.e. “A” and “B”. Subjects were distributed into two groups equally; Group A received a strengthening exercise approach and Group B received a stretching exercise approach. Data was analysed using SPSS version 25. Results: There was a statistically significant difference (p-value < 0.001) in pre- and post-treatment CVA and SA within each treatment group. However, no significant difference (p-value > 0.05) was reported across each treatment while comparing pre- and post-treatment values for CVA and SA respectively. Conclusion: Stretching and strengthening exercises are equally effective in the management of FHP and RS posture in asymptomatic individuals. However, strengthening exercise showed superior improvement in CVA and SA comparatively.